Readmissions after Pediatric Hospitalization for Suicide Ideation and Suicide Attempt. Issue 11 (1st November 2018) - Doupnik, Stephanie; Rodean, Jonathan; Zima, Bonnie T.; Coker, Tumaini R.; Worsley, Diana; Rehm, Kris P.; Gay, James C.; Hall, Matt; Marcus, Steve
Abstract : OBJECTIVE: To inform resource allocation toward a continuum of care for youth at risk of suicide, we examined unplanned 30‐day readmissions after pediatric hospitalization for either suicide ideation (SI) or suicide attempt (SA). METHODS: We conducted a retrospective cohort study of a nationally representative sample of 133, 516 hospitalizations for SI or SA among 6‐ to 17‐year‐olds to determine prevalence, risk factors, and characteristics of 30‐day readmissions using the 2013 and 2014 Nationwide Readmissions Dataset (NRD). Risk factors for readmission were modeled using logistic regression. RESULTS: We identified 95, 354 hospitalizations for SI and 38, 162 hospitalizations for SA. Readmission rates within 30 days were 8.5% for SI and SA hospitalizations. Among 30‐day readmissions, more than one‐third (34.1%) occurred within seven days. Among patients with any 30‐day readmission, 11% had more than one readmission within 30 days. The strongest risk factors for readmission were SI or SA hospitalization in the 30 days preceding the index SI/SA hospitalization (adjusted odds ratio [AOR]: 3.14, 95% CI: 2.73‐3.61) and hospitalization for other indications in the previous 30 days (AOR: 3.18, 95% CI: 2.67‐3.78). Among readmissions, 94.5% were for a psychiatric condition and 63.4% had a diagnosis of SI or SA. CONCLUSIONS: Quality improvement interventions to reduce unplanned 30‐day readmissions among children hospitalized for SI or SA should focus on children with a recent prior hospitalization and should be targeted to the first week following hospital discharge.